Mapeamento de competências: uma proposta de implantação de banco de talentos para a UNEMAT - Santos, Edneia Aparecida Souza Andrade (2021)
People management in public administration has evolved in line with the evolution of management models. Decree No. 5.707/2006 provides guidelines for these changes in people management to be implemented, despite resistance to organizational change. Intellectual capital in public administration has many trained people. However, public agencies do not always achieve effectiveness in their results, sometimes due to a lack of human capital allocated to perform more specialized activities. Thus, there is a search for managers for more efficient processes in public organizations. The management of competencies emerges as a possible tool for restructuring the human capital of institutions. This research aimed to map the skills of the technical- administrative servers and proposition of a talent bank prototype, supporting the institutional decision-making process regarding the training or redistribution of servers, and evaluate the possible adoption of management by competencies in a public HEI. The methodology used in the research was bibliographic, documentary, observation and case study, with on-line questionnaire as instruments of collection. A case study was carried out involving administrative university employees from the State University of Mato Grosso - UNEMAT, Campus of Nova Mutum - MT. The results indicated that the adoption of Management of competencies is fundamental for the development of management in a Higher Education Institution. A framework was proposed for a talent database at the institution.